P01.012 Tumor Treating Fields (TTFields) in combination with lomustine (CCNU) and temozolomide (TMZ) in patients with newly diagnosed glioblastoma (GBM). (19th September 2018) - Lazaridis, L; Schäfer, N; Kebir, S; Weller, J; Tzaridis, T; Scheffler, B; Pierscianek, D; Kleinschnitz, C; Stuschke, M; Sure, U; Herrlinger, U; Glas, M
Abstract: Introduction: TTFields in combination with TMZ showed significant survival benefit for newly diagnosed glioblastoma patients in the EF-14 trial, compared to TMZ standard therapy; independent of MGMT-promotor methylation-status, age and performance status. Recently, the CeTeG trial (NOA-09) demonstrated improved efficacy of lomustine (CCNU)/TMZ compared to TMZ standard therapy in newly diagnosed MGMT-promotor methylated GBM patients. Given that TTFields demonstrated a strong safety profile as well as a high potential being combined with other modalities and the very promising results for GBM patients with methylated MGMT-promotor in the CeTeG trial, there is a strong rationale in combining these modalities. This is the first report on patients, treated with a combination of both treatment regimens, TTFields and CCNU/TMZ. Methods: Patients with newly diagnosed GBM and MGMT-promoter methylation were treated after surgery and radiochemotherapy with a combination of TTFields plus CCNU/TMZ at our institutions. Patients with complete resection (N=4), partial resection (N=3) as well as biopsy (N=1) were included in the analysis. We assessed safety and feasibility of this combined therapy. Results: Currently, eight patients (medians: age 49, [39–69]; KPS 90, [70–100]) have been treated and analyzed: GBM IDH mutant (N=2), IDH wild-type (N=6). To-date, CTCAE grade 3 hematotoxicities were observed in two patients, but were not considered to be related to the addition of TTFields to CCNU/TMZ. No further non-hematologic toxicity was observed. In one patient a grade 3 event (herpes zoster) emerged. Regarding medical device site reactions, low-grade skin irritations were detected in four patients (50%), corresponding to the safety analysis from the EF-14 trial with low-grade skin irritations in 52% of the patients. Conclusion: These data provide first indications that the combination of TTFields and CCNU/TMZ is probably safe and feasible. Additional follow-up and a higher sample size are needed for further toxicity analysis and efficacy assessment of this combination.